Overview of the influence of ginger on reducing pregnancy emesis at Sartika Clinic in 2024 - S, R. Oktaviance.; Meisa, Manda; Veronika, Anita; Ambarita, Bernadetta (Science Midwifery, 2024)
In early pregnancy, nausea occurs because the hormones estrogen and HCG increase in the blood. Research Objective: To determine knowledge about the effect of boiled ginger water in reducing the frequency of nausea and vomiting in pregnant women in the 1st and 2nd trimester at the Sartika clinic in 2024. Research Method: This research is descriptive. The sampling technique was purposive sampling with a total of 15 respondents. Research Results: The research results show that knowledge in the good category is 8 people (53.3%), in the sufficient category is 5 people (33.3%), and in the low category is 2 people (13.3%). Conclusion: Based on the research results, it shows that TM 1 and 2 pregnant women have good knowledge about boiling ginger water to reduce the frequency of nausea and vomiting. It is hoped that health workers will continue to increase education about drinking ginger water so that the frequency of nausea and vomiting in pregnant women can be reduced.